2009
DOI: 10.1128/jvi.00671-08
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Activates Innate Immunity through Toll-Like Receptor 2

Abstract: Respiratory syncytial virus (RSV) is a common cause of infection that is associated with a range of respiratory illnesses, from common cold-like symptoms to serious lower respiratory tract illnesses such as pneumonia and bronchiolitis. RSV is the single most important cause of serious lower respiratory tract illness in children <1 year of age. Host innate and acquired immune responses activated following RSV infection have been suspected to contribute to RSV disease. Toll-like receptors (TLRs) activate innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
219
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(229 citation statements)
references
References 57 publications
3
219
1
Order By: Relevance
“…Furthermore, our findings suggest that the severe pathophysiological effects of influenza A virus are not TLR-3 mediated and may involve interaction of other influenza viral genetic determinants with additional pattern-recognition receptors, such as TLR-7. Finally, we should note that, since we found that TLR-2 agonists could also induce the same degree of AFC impairment as poly(I:C), we cannot exclude a role for TLR-2 activation in mediating this effect, particularly given the recent finding that activation of TLR-2 by RSV is involved in the innate immune response to this virus (39). However, because influenza also inhibits amiloride-sensitive AFC but has not been shown to activate TLR-2-mediated signaling, this possibility seems unlikely.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, our findings suggest that the severe pathophysiological effects of influenza A virus are not TLR-3 mediated and may involve interaction of other influenza viral genetic determinants with additional pattern-recognition receptors, such as TLR-7. Finally, we should note that, since we found that TLR-2 agonists could also induce the same degree of AFC impairment as poly(I:C), we cannot exclude a role for TLR-2 activation in mediating this effect, particularly given the recent finding that activation of TLR-2 by RSV is involved in the innate immune response to this virus (39). However, because influenza also inhibits amiloride-sensitive AFC but has not been shown to activate TLR-2-mediated signaling, this possibility seems unlikely.…”
Section: Discussionmentioning
confidence: 91%
“…To ensure clinical relevance, we built on our in vitro-derived mechanistic insights by examining how functional variants in NFKBIA alter in vivo susceptibility to childhood diseases with an inflammatory component in their pathogenesis: asthma, respiratory syncytial virus (RSV), bronchiolitis, and BPD. Although each of these clinical phenotypes has its own complex etiology, a central contribution of the innate immune system and NF-kB signaling is common to all (7)(8)(9)(10)(11)(12)(13). Greater understanding of the genetic control of the NF-kB pathway is particularly important given the growing interest in the identification of biomarkers that predict the risk for disease and the development of novel therapies that modulate NF-kB activity (14).…”
mentioning
confidence: 99%
“…The TLR2 Arg677Trp and Arg753Gln SNPs are associated with susceptibility and severity of viral infections. [25][26][27][28] In our laboratory we found the Phe707Phe polymorphism in the Mexican population, with an allelic frequency of 7.5% and this suggests that this SNP not affect our population. 29 The first line of defense against viruses is interferons.…”
Section: Immune Response and Risk Factorsmentioning
confidence: 89%
“…24 There are several studies showing that herpes simplex virus type 1 (HSV1), type 2 (HSV2), cytomegalovirus (CMV) and respiratory syncytial virus (RSV) induce TLR2-dependent proinflammatory cytokines in an attempt to induce cell protection. [25][26][27] On the other hand, single nucleotide polymorphisms (SNPs) in genes encoding TLRs have also been reported. The TLR2 Arg677Trp and Arg753Gln SNPs are associated with susceptibility and severity of viral infections.…”
Section: Immune Response and Risk Factorsmentioning
confidence: 99%